Gaya Kepemimpinan Kepala Dinas Pemadam Kebakaran Kota Makassar - Darwis, Masriani; Madani, Muhlis; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to find out the leadership style of the head at Makassar city fire department. The study  used qualitative, with 6 informants. Data collection techniques used the method of direct observation, in-depth interviews, and documentation. The results of this study showed that transformational leadership seen from charisma, inspiration, intelligence, and individualism had run well  because the head of the department used it been in every  conditions and situations faced when leading. While the ability of employees and members of the Makassar city fire service team personnel showed that they worked optimally without having directions from the Makassar city fire department head because they already had their main duties and functions according to their respective fields.